Constructing the composite indicator "Quality of work" from the third European survey on working conditions - Andranik S. Tangian (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2004)
The composite indicator "Quality of work" for comparing European countries is constructed from data of the Third European Survey on Working Conditions. The main findings are as follows: (a) European countries differ with respect to working conditions statistically more significantly than with respect to earnings; it implies a quite accurate discrimination threshold in ranking countries with respect to quality of work, (b) working conditions and earnings positively depend over the whole of Europe but little correlate within single countries; it indicates at the prevailing role of national determinants over professional or social specificities as contributing to the average quality of work, (c) earnings play no role in subjective satisfaction from work which exclusively depends on working conditions; consequently, more attention should be paid to improving the latter, (d) working conditions of women are significantly better than that of men, which is explained by their inclination to service occupations. Processing ordinal rather than metrical data requires an addendum to the methodology of composite indicators. The corresponding mathematical model is proposed.
Keywords: C43; J21; J88; C51; 330; Quality of work; European Union; composite indicators; statistical indices; processing ordinal data; Arbeitsbedingungen; Sozialer Indikator; Vergleich; EU-Staaten